Metalowa Płyta Warstwowa z Wypełniaczem Szkieletowym - Boroch, H. (Engineering Transactions, 1974)
A rectangular sandwich plate simply supported on its edges and subject to uniformly distributed vertical load is considered in the paper. The faces of the plate are connected with each other by a certain number of short rods of cylinders which constitute the core of the sandwich plate. Hinged connection with a rigid edge stiffener ensures the conditions of free support at the edges to be satisfied.